SWEET’S SYNDROME AS CUTANEOUS MARKER FOR UNDERLYING FOLLICULAR LYMPHOMA: AN ULTIMATELY FATAL RARE CASE REPORT. - DR.ANANDRAJ VAITHY.K; DR.VAISHALI DHANANJAY KOTASTHANE; DR. DHANANJAY KOTASTHANE. (International Journal of Pharma and Bio Sciences, 2015)
An elderly male patient presented with fever for one week, followed by multiple excoriated cutaneous lesions distributed over sun exposed areas of 15 days duration. Clinical diagnosis of erythematous skin lesions was considered and skin biopsy preceded by complete blood count was performed. Total Leukocyte Count was increased and peripheral smear showed leucocytosis with > 50% of cleaved cells. Skin biopsy showed features of the Sweet’s Syndrome and was started on corticosteroids. In view of peripheral smear findings, the patient was evaluated for staging of the disease. Lymph node enlarged in the right axillary region with moderate hepatosplenomegaly. Fine needle aspiration cytology from the lymph node showed diagnostic features of follicular lymphoma and a complete work up for grading was advised. Excision biopsy of lymph node showed features of low grade follicular lymphoma. The patient expired in a couple of days inspite of prompt and rigorous treatment. This patient presented only with features of Sweet’s syndrome and was incidentally diagnosed to have follicular lymphoma. Follicular lymphoma, even of low grade can present with skin lesions, with spill over in peripheral blood which could turn to be highly fatal.This highlights that elderly patients presenting with non- specific cutaneous lesions with hepatosplenomegaly should be evaluated to rule out possibility of underlying Hematological malignancy.